Social Entrepreneurship and the Development Paradox of Prosocial Motivation: A Cautionary Tale - McMullen, Jeffery S.; Bergman, Brian J. (Strategic Entrepreneurship Journal, 2017)
Research summary We provide an ethnographic account of how social entrepreneurs in the Safe Water for Africa program made sense of hybrid goods, as well as how and why those understandings affected both the social enterprise's marketing mix and stakeholders’ expectations of the enterprise's rights and responsibilities. We find that output maximizing‐behavior enabled by prosocial motivation elicits a psychological feeling of entitlement to a socio‐emotional return on investment in the form of beneficiary gratitude. When external stakeholders consider them justified, these feelings become moral norms that can induce or prevent the institutionalization of a suboptimal path of development, depending on the motivations of competitors. We show that social entrepreneurs’ emotional attachment can have consequences for development, challenging the functionalist conception of social enterprise as a temporary patch to institutional voids. Managerial summary We present a detailed account of the Safe Water for Africa program that examines: (a) how the program's stakeholders made sense of water as a “hybrid good;” and (b) how these understandings shaped the social entrepreneurs’ attitudes, the social enterprise's marketing mix, and stakeholder's expectations of the enterprise's rights and responsibilities. We find that the same motivation that prompted social entrepreneurs to act on behalf of those without safe water elicited a sense of entitlement to a “return on investment” in the form of beneficiary gratitude. If reciprocated, these feelings may become normalized and, depending on competitors' motives, hinder long‐term development efforts by precluding their entry. Copyright © 2017 Strategic Management Society.